Further studies on a bovine plasma medium that can be heat sterilized for Lactobacilli - Barboza, Yasmina; Márquez Salas, Enrique; Benítez, Betty; Izquierdo, Pedro (Revista Científica de la Facultad de Ciencias Veterinarias)
Preparation and efficiency of a bovine plasma medium (BPM), based on liquid or powder bovine blood plasma that can be heat sterilized, is described. Protein, amino acids, and pH of the medium were analyzed, The efficiency of the BPM was compared against a commercial medium (MRS) using L. plantarum, L. casei. L. bulgaricus and L. acidophilus. Individual effect of minerals and yeast extract were also tested. Results shown that BPM either from liquid or powder bovine plasma can be prepared by heat sterilization, remaining clear and without any turbidity if the pH is previously adjusted to 11. Final pH, protein and amino acid contents were similar when the BPM was prepared by either liquid or powder bovine plasma. When the efficiency of the new medium was compared against commercial MRS, no differences in the growth of the different Lactobacilli were observed. Mineral supplementation, was more efficient than yeast extract for Lactobacilli growth in BPM. Even without minerals and yeast extract supplementation, an important growth of Lactobacilli was observed when liquid or powder bovine plasma was used as a source of protein. It is concluded that new low cost, practical medium has been developed for the propagation of Lactobacilli.